The Implementation of VIKOR Method to Improve the Effectiveness of Sidi Learning Graduation - J B Parrangan, Yan; Mesran, M; Gaurifa, Suardin; Samsi Purba, Anton; Zebua, Perlin; Willem, W; Waruwu, Dermawan; Suginam, S; Kristianto Hondro, Rivalri; Simar, Janner; K Siburian, Henry; T Sianturi, Lince (International Journal of Engineering and Technology, 2018)
Sidi learning for the Christian community is one of the most important learning for Christians. Sidi teaches an understanding of the life given by God and understands the meaning of the death of Jesus Christ on the cross. Graduation for sidi participants is a responsibility for the assembly of church congregations. Graduation from learning sidi must go through several conditions such as attendance, test scores, leadership and attitudes which are also weighted on each criterion. In order for the results of the graduation to be more effective, a decision support system based on the method known as VIKOR was implemented.Â Â